ANALISIS PRAKTIK PENGHINDARAN PAJAK DI BIDANG IMPOR PADA KEPAILITAN PERUSAHAAN EKSPOR IMPOR - HIMAWAN YUSUF; JAKA ISQIYARTA (Jurnal BPPK : Badan Pendidikan dan Pelatihan Keuangan, 2019)
ANALYSIS OF IMPORT TAX AVOIDING PRACTICES IN THE BANKRUPTCY OF EXPORT-IMPORT COMPANIES. Import tax is a high tax burden for the company. This makes some company try to reduce the import tax burden, one of which is to utilize a bankruptcy. The study aims to analyze the practice of import tax avoidance in the bankruptcy of companies and its accompanying motivation and to analyze about the effectiveness of Customs actions to prevent the practice of tax avoidance. Qualitative methods with a case study approach are used to analyze tax avoidance practices in bankruptcy of three import-export companies which were then called by the initials XYZ. Based on the results of the analysis, it is concluded that there has been a practice of tax avoidance with various motivations. Customs action to prevent the practice of tax avoidance has been less effective due to various constraints.